NIKOLAI IVANOVICH VAVILOV AT THE AMUR AGRICULTURAL EXPERIMENTAL STATION - O. O. Kletkina; V. T. Sinegovskaya (Вавиловский журнал генетики и селекции, 2015)
The article describes the visit of Аcademician N.I. Vavilov to the Amur agricultural experimental station in 1920s. The station was located at the site of the former Ozerki postal station, presently Sadovoe Village, Tambov raion, Amur oblast. In this year, the Amur experimental station (presently All-Russia Soybean Research Institute) celebrates its 105th anniversary.